Attenuation of Circulating Trimethylamine N-Oxide Prevents the Progression of Cardiac and Renal Dysfunction in a Rat Model of Chronic Cardiorenal Syndrome - Zou, Deling; Li, Yanyu; Sun, Guangping (Frontiers in Pharmacology, 2021)
Chronic heart failure (HF) frequently causes progressive decline in kidney function, known as cardiorenal syndrome-2 (CRS2). Current treatment options for CRS2 remain unacceptably limited. Trimethylamine-N-oxide (TMAO), a metabolite of gut microbiota, has recently been implicated in the pathogenesis of both HF and chronic kidney disease. Here we examined whether circulating TMAO is elevated in CRS2 and if so, whether attenuation of circulating TMAO would ameliorate the progression of CRS2. Sprague-Dawley rats underwent surgery for myocardial infarction (MI) or sham (week 0) followed by 5/6 subtotal nephrectomy (STNx) or sham at week 4 to induce CRS2 or control. At week 6, MI + STNx rats and control rats received vehicle or 1.0% 3,3-Dimethyl-1-butanol (DMB, a TMAO inhibitor) treatment for 8 weeks. Compared with control rats, MI + STNx rats exhibited elevated serum TMAO at week 6, which was increased further at week 14 but was attenuated by DMB treatment. MI + STNx rats showed cardiac dysfunction as assessed by echocardiography and renal dysfunction as evidenced by increased serum creatinine and urinary kidney injury molecule-1 and decreased creatinine clearance at week 6. The cardiac and renal dysfunction in MI + STNx rats was exacerbated at week 14 but was prevented by DMB treatment. Molecular and histological studies revealed myocyte hypertrophy and increases in interstitial myocardial fibrosis and gene expression of pro-hypertrophic and pro-fibrotic markers in both heart and kidney at week 14, which were accompanied by elevated gene expression of proinflammatory cytokines. The changes in molecular and histological parameters observed in MI + STNx rats were significantly reduced by DMB treatment. These findings suggest that rats with CRS2 have elevated circulating TMAO, which is associated with the exacerbation of cardiac and renal dysfunction. Attenuation of circulating TMAO can ameliorate cardiac and renal injury and prevents the progression of CRS2.